Síntese mecanoquímica do cocristal de ácido salicílico com ácido nicotínico - Ferreira, Laura Teófilo [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The preliminary study of the selected reagents showed that the NCO does not undergo polymorphic transition during the grinding process, under the conditions adopted, however the SA presented structural alterations in the X-ray diffractograms, the DSC curve discarded the possibility of forming a polymorph of SA, however the direct test for Fe3+ indicated the presence of the ion in the milled sample, it was observed the disappearance of the phenol characteristic band (present in SA) in the FTIR spectrum, indicating the formation of a complex between SA and Fe3+. A screening was done using the salicylic acid and nicotinic acid APIs by means of the mechanochemical synthesis to try to obtain cocristais from these compounds. The X-ray diffraction patterns were efficient for the study of crystalline structures compounds. When comparing the diffractograms, it was observed that the NCO SA 1: 1 and 2: 1 systems were diffractograms sum of the API and coformador, indicating that there were no interactions between the compounds, however the 1: 2 system diffractogram showed evidence of obtaining cocristal. The FTIR technique provided important information on the sites of interaction between the molecules, showing that 1: 1 and 2: 1 NCO SA systems did not interact, and that the 1: 2 system interacted, confirming also the stoichiometry used in the synthesis. Thermal analysis techniques were essential to provide information on the thermal behavior of compounds and mixtures, indicating the formation of eutectic compounds in the 1: 1 and 2: 1 systems and confirming the obtaining of the cocrystal in the 1: 2 system by means of the DSC curves, the TG-DTA curves showed information on the thermal stability of these compounds and assisted in the analysis of the DSC curves

O estudo preliminar dos reagentes selecionados mostrou que o ácido nicotínico (NCO) não sofre transição polimórfica durante o processo de moagem, nas condições adotadas, no entanto o ácido salicílico (SA) apresentou alterações estruturais nos difratogramas de raios X, a curva de DSC descartou a possibilidade de formação de um polimorfo de SA, o teste direto para Fe3+ mostrou a presença do íon na amostra moída, o FTIR indicou a formação de um complexo entre SA e Fe3+. Realizou-se uma triagem utilizando os APIs ácido salicílico e ácido nicotínico por meio da síntese mecanoquímica para tentativa de obtenção de cocristais desses compostos. Os difratogramas de raios X foram eficientes quanto ao estudo das estruturas cristalinas dos compostos. Ao comparar os difratogramas observou-se que os sistemas NCO SA 1:1 e 2:1 eram difratogramas soma do NCO e SA, indicando que não houve interações entre os compostos, no entanto o difratograma do sistema 1:2 mostrou indícios de obtenção de cocristal. A técnica de FTIR forneceu informações importantes sobre os sítios de interação entre as moléculas, mostrando que os sistemas NCO SA 1:1 e 2:1 não interagiram, e que o sistema 1:2 interagiu, confirmando também a estequiometria utilizada na síntese. As técnicas de analise térmicas foram essenciais para fornecimento das informações sobre o comportamento térmico dos compostos e das misturas, indicando a formação de compostos eutéticos nos sistemas 1:1 e 2:1 e reconhecendo a obtenção do cocristal no sistema 1:2 por meio das curvas de DSC, as curvas TG-DTA mostraram informação sobre a estabilidade térmica desses compostos e auxiliaram na analise das curvas DSC
Keywords: Cristalização; Acido salicilico; Estrutura quimica; Testes quimicos e reagentes; Niacina